Calibration and test of DIFAR sonobuoys - Kuzu, Ahmet; Danis, Uveys; Kurt, Engin; Karabulut, Engin; Sahinkaya, Demet; Bilgic, Eyup; Kaplaner, Ahmet; Birecik, Serdar (IEEE, 2011)
In this paper, a method for calibrating and testing DIFAR sonobuoy multiplexer without sea or water is proposed. For this purpose; the architecture of DIFAR sonobuoy is introduced, calibration factors are expressed, calibration and test environment in terms of hardware and software are described, calibration and test procedure is explained, and finally, advantages and disadvantages of the proposed calibration and test method is discussed.